Resilient modulus prediction of nano-silica modified porous asphalt using finite element analysis - Putra Jaya, Ramadhansyah; Al-Akhshar, A. M.; K. A., Masri; A. H., Norhidayah; M. N., Mohd Warid; H., Yaacob (IOP Publishing Ltd, 2021)
Repetitive traffic load is the most important factor influencing porous asphalt (PA) performance. The performance of asphalt is mostly influenced by the loading magnitude of heavy vehicles. In order to improve the service performance of PA under heavy traffic conditions. the decrement of stiffness is one of the failures that occur on the PA which mainly caused by the repeated load from a large number of different types of vehicles which leads to reduce the characteristic of PA in terms of stiffness and durability. Moreover, to enhance the performance of PA against the stiffness reduction an additive material used to increase the strength of the PA called Nano-silica particles. Thus, the aim of the study to investigate the resilient modulus of Nano-silica modified PA and develop a finite element analysis FEA model to predicate the resilient modulus. In this study, three different Nano-silica contents 0%, 2% and 4% by weight of PA mixture were investigated. To achieve this, a finite element model was developed and simulated by using ABAQUS 6.14 software for the PA samples to predict the resilient modulus performance. A comparative study was done among the unmodified and modified PA mixtures considering the resilient modules value. The result showed that Nano-silica is recommended as an additive in PA mixture, as the result of the modified PA mixture with 2% of NS was 4357Mpa while the unmodified was 3001Mpa. Thus, the addition of NS to PA mixture Capable in increasing the strength and quality of asphalt mixture.